Prolonged cerebral circulation time is more associated with symptomatic carotid stenosis than stenosis degree or collateral circulation. (30th August 2017) - Hu, Yong-Sin; Guo, Wan-Yuo; Lee, I-Hui; Chang, Feng-Chi; Lin, Chung-Jung; Lin, Chun-Jen; Luo, Chao-Bao; Wu, Chih-Chun; Lee, Han-Jui
Abstract : Background and purpose: Current practice of revascularization for carotid stenosis (CS) primarily relies on symptoms and degree of stenosis. Other parameters, such as collateral circulation and cerebral circulation time (CCT), might influence the stroke risk in CS. This study was conducted to (1) investigate whether CCT is more associated with symptomatic CS than degree of stenosis and (2) elucidate the associations among the degree of stenosis, collateral status, and CCT. Methods: From 2010 to 2016, 82 patients with unilateral CS were enrolled for DSA and divided into symptomatic and asymptomatic groups based on clinical presentation. CCT was defined as the difference between the time taken by the cavernous internal carotid artery and parietal vein to reach the maximal contrast medium intensities on lateral DSA. The degree of stenosis, collateral status, and CCT of the two groups were compared. Logistic regression analysis was performed to estimate the OR for symptomatic CS with the imaging variables. Results: The symptomatic group had a significantly higher degree of stenosis and longer CCT. CCT (OR 1.95, p=0.013) was more associated with symptomatic CS than the degree of stenosis (OR 1.03, p = 0.229), after adjustment for potential confounders—namely, age, sex, antithrombotic use, and collateral status. Symptomatic high grade CS with collaterals had a non-significantly shorter CCT than those without collaterals. Conclusions: DSA derived CCT is more reflective of the hemodynamic differences between symptomatic and asymptomatic CS than degree of stenosis. Collaterals may not effectively reduce CCT in symptomatic high grade CS.